Assertiveness : how can I say what I mean? - Havelin, Kate (South Africa: LifeMatters, Mankato, Minn., 2000)
Defines assertiveness, discusses its value, and offers strategies for readers to improve their assertiveness skills
Juvenile works
Keywords: Assertiveness (Psychology) -- Philosophy; Assertiveness in adolescence